Knowledge, Attitude, and Beliefs of Communities and Health Staff about Echinococcus granulosus Infection in Selected Pastoral and Agropastoral Regions of Uganda - Othieno, Emmanuel; Ocaido, Michael; Mupere, Ezekiel; Omadang, Leonard; Oba, Peter; Okwi, Andrew Livex (Journal of parasitology research, 2018)
According to World Health Organization (WHO) [1] cystic echinococcosis (CE) is a neglected zoonotic infection found throughout the world and is associated with high morbidity and mortality in poor resource countries especially in pastoral communities in Africa (Macpherson et al. [2]). In Uganda, the prevalence ofCE has been found to vary between pastoral and agropastoral communities, with pastoral communities being at higher risk than agropastoral communities (Othieno et al. [3]). High prevalence of CE has equally been reported in livestock (Chamai et al. [4] and Magambo et al. [5]) and in dogs (Inangolet et al. [6] and Oba et al. [7]). Cystic echinococcosis is caused by a species of Echinococcus, namely, Echinococcus granulosus, whose definitive hosts are the carnivores such as dogs. Usually dogs become infected with Echinococcus granulosus by eating infected internal organs such as liver and lungs from dead animals that contain tape worm embryos. The dogs pass out tapeworm eggs in their stool, which can cause infection in other animals and/or in humans who accidentally swallow the eggs. In humans, Echinococcus granulosus forms slow-growing cysts (called hydatid cysts) in different organs of the body which can be very difficult to remove or treat in some cases (Nahmias et al. [8]).
Keywords: Knowledge; Attitude; Communities; Echinococcus granulosus Infection; Pastoral and Agropastoral Regions